2022
DOI: 10.1136/bmjopen-2021-057404
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception and preventive behaviours of COVID-19 among university students, Gondar, Ethiopia: a cross-sectional study

Abstract: ObjectiveThis study aimed to assess COVID-19 preventive behaviours and their associated factors among university students.MethodsAn institution-based cross-sectional study was employed among 405 university students and the study participants were chosen using a stratified simple random selection procedure. A pretested self-administered questionnaire was used to assess participants’ perception of and preventive behaviour towards COVID-19. A multivariable logistic regression analysis was employed to identify fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(60 reference statements)
3
5
0
Order By: Relevance
“…Age, sex, knowing a COVID-19 infected person, perceived vulnerability, and the type of program they had registered in all had an impact on students' COVID-19 preventative behavior. The results also showed that in order to increase this population's COVID-19 preventive behavior, health communication interventions aiming at altering people's views of COVID-19 and related preventative methods are urgently needed (Tsegaw et al, 2022). Moreover, the results of this investigation are consistent with those of a study that was conducted in Saudi Arabia among student nurses.…”
Section: Discussion Of the Findingssupporting
confidence: 84%
“…Age, sex, knowing a COVID-19 infected person, perceived vulnerability, and the type of program they had registered in all had an impact on students' COVID-19 preventative behavior. The results also showed that in order to increase this population's COVID-19 preventive behavior, health communication interventions aiming at altering people's views of COVID-19 and related preventative methods are urgently needed (Tsegaw et al, 2022). Moreover, the results of this investigation are consistent with those of a study that was conducted in Saudi Arabia among student nurses.…”
Section: Discussion Of the Findingssupporting
confidence: 84%
“…The low level of compliance with NPIs in our study is comparable to a study in South-South, Nigeria, which showed very low effective use of facemasks among university students [11]. Studies in Ethiopia [21] and Egypt [22] also revealed a low level of adherence to Covid-19 preventive measures among university students.…”
Section: Discussionsupporting
confidence: 74%
“…It is worth noting that the way people perceive COVID-19 is significantly associated with their worries and preventing behaviors [ 27 ]. In a similar study, it was found that less than 45.7% of nursing students had adequate preventive behaviors toward COVID-19 [ 28 ], while Shahwan et al [ 29 ] found that more than half of the students were misunderstanding the most frequent symptoms of COVID-19, such as nausea, vomiting, and diarrhea, and had little knowledge about the transmission of COVID-19. However, participants of an increased age had better COVID-19 preventive behavior than young participants possibly due to their high perceived susceptibility [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the preventive behavior of nursing students is related to the knowledge they receive about COVID-19 transmission and prevention in the university where they study [ 35 ]. Thus, the appropriate education about pandemic risk perception can help students comply with COVID-19 preventive practices [ 28 ]. Moreover, websites of government and international organizations, social media, and published scientific articles can provide adequate information about COVID-19 prevention measures and vaccination to university students [ 32 ].…”
Section: Discussionmentioning
confidence: 99%